2015
DOI: 10.4012/dmj.2014-115
|View full text |Cite
|
Sign up to set email alerts
|

Shear-bond-strength of orthodontic brackets to aged nano-hybrid compositeresin surfaces using different surface preparation

Abstract: The aim of this study was to evaluate the effects of different surface preparation methods on the shear bond strength (SBS) of orthodontic metal brackets to aged nano-hybrid resin composite surfaces in vitro. A total of 100 restorative composite resin discs, 6 mm in diameter and 3 mm thick, were obtained and treated with an ageing procedure. After ageing, the samples were randomly divided as follows according to surface preparation methods: (1)Control, (2)37% phosphoric acid gel, (3)Sandblasting, (4)Diamond bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…In the current study, aging was performed by water storage for 24 hours and thermocycling between 5-55°C for 5000 cycles at first and 2000 cycles later. Thermocycling accelerates the process of aging and water diffusion (22). Temperature difference between water baths in this process results in water sorption at the interface of the two materials with different coefficients of thermal expansion and eventually degrades the resin structure (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, aging was performed by water storage for 24 hours and thermocycling between 5-55°C for 5000 cycles at first and 2000 cycles later. Thermocycling accelerates the process of aging and water diffusion (22). Temperature difference between water baths in this process results in water sorption at the interface of the two materials with different coefficients of thermal expansion and eventually degrades the resin structure (23).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the results of ARI scores showed that most sandblasted samples experienced fracture in the composite base. Demirtas et al , in 2015 reported the highest SBS following sandblasting with Al2O3 particles; they suggested this method to increase the bond strength of brackets due to minimal area of the prepared surface (22). Bayram et al , in 2011 reported the highest bond strength following surface roughening by diamond bur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with Hamano et al 33,34 . as the dentin bonding agent was not mixed with acetone instead the acetone was applied separately similar to Hamano et al 33 There was an agreement 15,21,35 that mechanical methods of surface treatment provided a significant increase in bond strength in composite to composite adhesion. According to Bayram et al 21 , Al2O3 particle abrasion and roughening with bur resulted in the highest SBS.…”
Section: Surface Treatmentmentioning
confidence: 95%
“…The bond strength of brackets can be effected by the surface preparation techniques, 27 bonding technique, 28 and the type of bonding materials. 29 Similarly, our results demonstrated that the type of bonding agent is important for the shear bond strength.…”
Section: Discussionmentioning
confidence: 99%